2019
DOI: 10.1371/journal.ppat.1008228
|View full text |Cite
|
Sign up to set email alerts
|

Novel replisome-associated proteins at cellular replication forks in EBV-transformed B lymphocytes

Abstract: Epstein-Barr virus (EBV) is an oncogenic herpesvirus and WHO class 1 carcinogen that resides in B lymphocytes of nearly all humans. While silent in most, EBV can cause endemic Burkitt lymphoma in children and post-transplant lymphoproliferative disorders/lymphomas in immunocompromised hosts. The pathogenesis of such lymphomas is multifactorial but to a large extent depends on EBV’s ability to aggressively drive cellular DNA replication and B cell proliferation despite cell-intrinsic barriers to replication. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 67 publications
(76 reference statements)
1
11
1
Order By: Relevance
“…Flow cytometry was performed as previous described ( Xu et al, 2019a ). Briefly, HEK-293T and A549 cells were transfected with EV, FLAG-ORF3a, FLAG-ORF-E, or FLAG-ORF-8.…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometry was performed as previous described ( Xu et al, 2019a ). Briefly, HEK-293T and A549 cells were transfected with EV, FLAG-ORF3a, FLAG-ORF-E, or FLAG-ORF-8.…”
Section: Methodsmentioning
confidence: 99%
“…With SZF1 being a DNA binding protein and its association, albeit low level, observed throughout the viral genome in sorted lytic cells ( S1 Fig ), we also asked if SZF1 might contribute to viral DNA replication originating from the lytic origins of replication. We therefore isolated nascent DNA using iPOND [ 29 ] from lytic-trigger exposed cells and found that while EA-D, as expected, was enriched at viral replication forks, SZF1 was not; consistent with pull-down of nascent viral DNA, the presence of PAA, a viral DNA polymerase inhibitor, demonstrated a reduction in DNA-bound EA-D ( Fig 8D ). Thus, on lytic genomes, SZF1 i) is enriched at the latent origin of replication, known to be silent during the lytic phase and ii) is not associated with actively replicating viral DNA.…”
Section: Resultsmentioning
confidence: 53%
“…1×10 8 HH514-16 cells were induced with 3mM NaB with or without phosphonoacetic acid (PAA) (200 μg/ml) for 36 hours prior to performing iPOND as described previously [ 29 ]. Briefly, cells were pulsed with 10 μM EdU for 15 min, spun down, cross-linked with 1% formaldehyde for 20 min, and quenched with 0.125 M glycine for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Zinc finger proteins (ZFP), the most widely occurring transcription actors which bind to nucleic acids and other molecules, play important roles in host immune response, and many of them are linked with carcinogenic processes and are involved in viral infections too. 79,80 Although there are no reports that directly involve ZNF428 with viral infections or processes related to cell division, several ZFPs have differentially expressed in various proteomic studies that demonstrate their participation in different mechanisms triggered by viral infections, such as endoplasmic reticulum stress and autophagy, 81 as well as alterations in DNA binding mediated by the inhibition of heat shock proteins 79 and forming part of replication forks, S-phase cell proliferation, and cell death. 80 All of these down-regulated molecules could be proteins affected by an inhibitory mechanism of cell division caused by PRRSV with the goal of ensuring its survival.…”
Section: ■ Discussionmentioning
confidence: 99%